Voltage-Mode Biquad Multifunction Filter Using VCIIs - Pitaksuttayaprot, Koson; Ritnathikul, Somkid; Jaikla, Winai (My University, 2022)
This paper describes a three-input, single-output, second-order filter with five responses, low-pass, high-pass, band-pass, band-reject, and all-pass functions, based on second-generation voltage conveyor (VCII). Both the quality factor and the pole frequency can be adjusted orthogonally. The proposed circuit is comprised of three VIIs, two capacitors, and six resistors. To obtain five filtering responses, the input signal applied into the input voltage nodes does not have to be doubled for the filter. Each filtering biquad function can be chosen by digitally selecting the appropriate input signals to input nodes of the filter. The output voltage node of the proposed multifunction filter is low impedance. The PSPICE application was used to design and simulate the filter. The simulation results from PSPICE are presented to validate the functionality of the presented versatile biquad filter. The simulation results coincide with the theoretical prediction very well.
Keywords: Analog filter; Multiple-input single-output configuration; VCII